Insomnia and hypertension: A systematic review. (October 2018) - Jarrin, Denise C.; Alvaro, Pasquale K.; Bouchard, Marc-André; Jarrin, Stephanie D.; Drake, Christopher L.; Morin, Charles M.
Summary: Insomnia is a prevalent sleep disorder that is associated with a multitude of health consequences. Particularly, insomnia has been associated with cardiovascular disease and its precursors, such as hypertension and blood pressure (BP) non-dipping. The present systematic review aimed to summarize the evidence on the concurrent and prospective associations between insomnia and hypertension and/or BP. Using electronic search engines (PubMed, SCOPUS, PsycINFO), 5, 618 articles published from January 1970 to December 2017 were identified, and 64 met the inclusion criteria (26 to 162, 121 participants; age range: 18–100; 46.4% male). Insomnia was based on diagnostic or non-diagnostic criteria. Hypertension was based on self-or physician-reports, antihypertensive medication use, and/or measured BP. Findings indicate that when insomnia is frequent, chronic, and/or accompanied with short sleep duration or objective markers of arousal, there is a strong association with hypertension/BP. Based on limited studies, hypertension did not significantly predict future insomnia in middle-aged adults, but did in older adults. Based on a majority of case–control studies, no differences in BP were found between participants with and without insomnia. Further research is needed to identify putative pathophysiological mechanisms underlying the link between insomnia and hypertension. The impact of insomnia therapy on BP should also be further examined in the future.